ANALYSIS OF COST AND REVENUE : EMPIRICAL STUDY OF BUSINESS UNIT WAKAF ANISA BAKERY - Triyawan, Andi; Prastyaningsih, Ika; Nabila Dwi Syahreni (Program Studi Magister Ekonomi Syariah UIN Ar-Raniry, 2023)
The aim of this research was to examine the expenses and revenue of the Annisa Bakery Gontor Putri Campus 1 business division. A qualitative descriptive method was utilized, employing a case study approach at the Mantingan branch of the Annisa Bakery Business Unit located in Ngawi, East Java. Data was collected through financial records encompassing both costs and sales generated during a single production cycle. The findings of this study reveal that the average monthly revenue obtained by the Annisa Bakery business unit amounted to IDR 46,336,500, while the total expenses incurred by the business unit amounted to IDR 18,817,500. Moreover, the analysis indicates that the bread business conducted by the Annisa Bakery business unit is considered feasible, as the R/C ratio exceeds 1, with a value of 3.40.